Analisis Sengketa Pajak dalam Kasus Gugatan Pajak Akuisisi Tanah dan Bangunan (Studi Kasus Putusan Pengadilan Pajak Nomor 002482.99/2020/PPM.XIVB) - Efendi Ibnususilo; Beni Murtadi; Suparto Suparto (SENTRI: Jurnal Riset Ilmiah, 2026)
Disharmony between taxpayers and the government leads to tax disputes, often caused by differences in calculations regarding the amount of tax payable. Similarly, in land and building sales transactions, tax disputes can arise due to differences in calculations between the seller and buyer and the government (Regional Government) regarding the amount of Income Tax and Land and Building Tax (BPHTB) payable. In practice, tax disputes sometimes arise due to the issuance of a Tax Underpayment Assessment Letter (SKPKB). This study aims to analyze the legal interpretation of the 2021 Tax Court Decision Number PUT-002482.99/2020/PP/MXIVB regarding the BPHTB Lawsuit Case. This research uses a normative legal approach. This research is legal research that uses a legislative and conceptual approach. The results of the study indicate that the tax appeal filed by PT. SAM in the Tax Court contains procedural errors that are not in accordance with legal principles because the principle of filing an appeal, where the description of the BPHTB calculation is not the object of the tax appeal dispute, because the object of the substance of the tax dispute is the decision of the tax collector in the form of objections to SKPDKB, SKPDKBT, SKPDKLB, SKPDN. The settlement of tax disputes at the appeal level has not yet received a decision on tax objections that are contrary to the requirements and procedures for appeal as stipulated in Article 31 and Article 35 of Law Number 14 of 2002 concerning the Tax Court. In conjunction with Article 103 and 104 of Law Number 28 of 2009 concerning PDRD. This fundamental misunderstanding between the object of the lawsuit and the object of the appeal is what causes taxpayers to lose the legal basis to fight for their rights from the outset.